2006
DOI: 10.1111/j.1600-0463.2006.apm_461.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression of GDP‐L‐fucose‐synthesizing enzymes, GDP‐fucose transporter and fucosyltransferase VII

Abstract: L-fucose is a fundamental monosaccharide component of many mammalian glycoproteins and glycolipids. Fucosylation requires GDP-L-fucose as a donor of fucose and a specific fucosyltransferase (Fuc-T) to catalyze the transfer of L-fucose to various lactosamine acceptor molecules. The biosynthesis of GDP-L-fucose consists of two pathways. The constitutively active de novo pathway involves conversion of cellular GDP-D-mannose to GDP-L-fucose by GDP-D-mannose-4,6-dehydratase (GMD) and GDP-4-keto-6-deoxy-D-mannose-3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…Studies conducted in mouse and human cell lines have shown a positive correlation of the expression of genes in de novo fucose synthesis pathway with the GDP-L-fucose levels in the cytosol [41]. Therefore, the increased expression of TSTA3 , GMDS and SLC35C1 indicates increased synthesis of GDP-L-Fucose in transition milk.…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted in mouse and human cell lines have shown a positive correlation of the expression of genes in de novo fucose synthesis pathway with the GDP-L-fucose levels in the cytosol [41]. Therefore, the increased expression of TSTA3 , GMDS and SLC35C1 indicates increased synthesis of GDP-L-Fucose in transition milk.…”
Section: Resultsmentioning
confidence: 99%
“…In the alternative salvage metabolism, that utilizes L-Fuc obtained from extracellular sources or from intracellular degradation of glycoproteins and glycolipids, L-fucokinase ( FUK gene) and GDP-L-fucose pyrophosphorylase ( FPGT gene) are involved. After synthesis in the cytosol, GDP-L-Fuc is translocated into the Golgi apparatus via a specific GDP-fucose transporter encoded by gene FUCT1/SLC35C1 [143, 144]. Because in D1 and D2 samples GMSD and TSTA3 gene were highly expressed relative to FPGT and FUK we suggesting that in GMSC the de novo pathway is preferentially activated and that a high amount of fucose is synthesized in cytoplasm ready to be imported in Golgi apparatus for fucosylation.…”
Section: Discussionmentioning
confidence: 99%
“…To understand what cell processes could be affected by these expression variations, we classified the 31 genes according to their function [23-51] (Table 2). We showed that a large part of these genes encoded adhesion proteins (around 30%), and only one of them was down-regulated.…”
Section: Resultsmentioning
confidence: 99%